2000
DOI: 10.1590/s1415-47572000000300009
|View full text |Cite
|
Sign up to set email alerts
|

Localization of genes modulating the predisposition to schizophrenia: a revision

Abstract: The genetics of schizophrenia or bipolar affective disorder has advanced greatly at the molecular level since the introduction of probes for the localization of specific genes. Research on gene candidates for susceptibility to schizophrenia can broadly be divided into two types, i.e., linkage studies, where a gene is found near a specific DNA marker on a specific chromosome, and association studies, when a condition is associated with a specific allele of a specific gene. This review covers a decade of publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Covariation analyses performed on behavioral data from a subset of the dyslexic twins in the Colorado Twin Study of Reading Disorders suggest that the same genes account for 95% of the comorbidity between ADHD and dyslexia (Willcutt et al 2000). In addition to being linked to dyslexia, the p21-23 region of chromosome 6 has been linked to schizophrenia (Goei et al 1998, Lopes-Machado and Duarte 2000, Ramsay 2000, Wright et al 2001 and ADHD (Barr et al 2000, Odell et al 1997, Warren et al 1995a, 1995b. One study found linkage of an ADHD phenotype to 6p21.3 in a population of dyslexics (Smith et al 2000).…”
Section: Modes Of Transmission Of Spoken Language Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Covariation analyses performed on behavioral data from a subset of the dyslexic twins in the Colorado Twin Study of Reading Disorders suggest that the same genes account for 95% of the comorbidity between ADHD and dyslexia (Willcutt et al 2000). In addition to being linked to dyslexia, the p21-23 region of chromosome 6 has been linked to schizophrenia (Goei et al 1998, Lopes-Machado and Duarte 2000, Ramsay 2000, Wright et al 2001 and ADHD (Barr et al 2000, Odell et al 1997, Warren et al 1995a, 1995b. One study found linkage of an ADHD phenotype to 6p21.3 in a population of dyslexics (Smith et al 2000).…”
Section: Modes Of Transmission Of Spoken Language Disordersmentioning
confidence: 99%
“…The proximity of the 6p21-23 dyslexia locus to the HLA 31 Because this child had a performance IQ of only 74 (verbal IQ 70), the anomalies noted on autopsy may be related to general cognitive impairment rather than spoken-language impairment. 32 A number of researchers have suggested that the incidence of autoimmune disorders is also elevated in schizophrenia, ADHD, and autism (Geschwind & Galaburda 1987, Lopes-Machado & Duarte 2000, Odell et al 1997, Warren et al 1995a. Not all studies are in agreement, however (Jacobsen et al 1999). locus and the proximity of the 15q21-23 dyslexia locus to the beta2-microglobin gene (which has been implicated in human autoimmune system, Lazarus & Owen 1994) provides additional support for some version of the dyslexia/immune dysfunction theory.…”
Section: Modes Of Transmission Of Spoken Language Disordersmentioning
confidence: 99%
“…8 Some studies suggest the existence of a gene locus located in the short arm of chromosome 6, which provides susceptibility for this psychiatric disorder; it is possible that this locus is located inside the HLA complex. 10 The first publications about the association of schizophrenia with HLA focused on class I HLA, whereas the most recent ones have focused on class II HLA. Although Wright et al have found higher frequency of antigens HLA-A9, HLA-A24, HLA-A19 and HLA-A28, 7 Gibson et al…”
Section: Schizophreniamentioning
confidence: 99%